The Effect of the Field Trip Learning Method on Student Activeness and Learning Outcomes at Junior high school - Titik Supaida; Kustiyowati Kustiyowati; Eges Triwahyuni (Postgraduate, University of Mataram, 2025)
This study aimed to examine the effect of the Field Trip learning model on student activeness and learning outcomes in English subjects. The research employed a quasi-experimental design with two groups, namely the experimental class that received Field Trip-based instruction and the control class that used conventional teaching methods. Data were collected through observation sheets to measure student activeness and pretest–posttest instruments to assess cognitive learning outcomes. The findings revealed that students in the experimental class demonstrated higher levels of participation, especially in asking questions, discussing, and drawing conclusions, compared to the control class. Furthermore, the posttest scores of the experimental group were significantly higher, indicating that the Field Trip model effectively enhanced students’ cognitive achievement. These results suggest that learning through direct experience can foster meaningful engagement and strengthen conceptual understanding. Practically, the Field Trip model can serve as an alternative strategy to improve classroom interaction and academic performance. Theoretically, this study supports the constructivist view that knowledge is better constructed through contextual and experiential learning. It is concluded that the Field Trip learning model not only improves academic outcomes but also contributes to the development of twenty-first century skills